A novel role of fragile X mental retardation protein in pre-mRNA alternative splicing through RNA-binding protein 14. (4th May 2017) - Zhou, Lin-Tao; Ye, Shun-Hua; Yang, Hai-Xuan; Zhou, Yong-Ting; Zhao, Qi-Hua; Sun, Wei-Wen; Gao, Mei-Mei; Yi, Yong-Hong; Long, Yue-Sheng
Highlights: FMRP interacts to RNA-binding protein 14 (RBM14). Loss of FMRP alters the alternative splicing of Protrudin and Tau . Knockdowns of FMRP and RBM14 show similar splicing pattern. FMRP is involved in alternative splicing via RBM14. Over expressions of FMRP-associated isoforms of Protrudin and Tau promote protrusion growth. Abstract: Fragile X mental retardation protein (FMRP), an important RNA-binding protein responsible for fragile X syndrome, is involved in posttranscriptional control of gene expression that links with brain development and synaptic functions. Here, we reveal a novel role of FMRP in pre-mRNA alternative splicing, a general event of posttranscriptional regulation. Using co-immunoprecipitation and immunofluorescence assays, we identified that FMRP interacts with an alternative-splicing-associated protein RNA-binding protein 14 (RBM14) in a RNA-dependent fashion, and the two proteins partially colocalize in the nuclei of hippocampal neurons. We show that the relative skipping/inclusion ratio of the micro-exon L in the Protrudin gene and exon 10 in the Tau gene decreased in the hippocampus of Fmr1 knockout (KO) mice. Knockdown of either FMRP or RBM14 alters the relative skipping/inclusion ratio of Protrudin and Tau in cultured Neuro-2a cells, similar to that in the Fmr1 KO mice. Furthermore, overexpression of FMRP leads to an opposite pattern of the splicing, which can be offset by RBM14 knockdown. RNA immunoprecipitation assays indicate that FMRP promotes RBM14's binding to the mRNA targets. In addition, overexpression of the long form of Protrudin or the short form of Tau promotes protrusion growth of the retinoic acid-treated, neuronal-differentiated Neuro-2a cells. Together, these data suggest a novel function of FMRP in the regulation of pre-mRNA alternative splicing through RBM14 that may be associated with normal brain function and FMRP-related neurological disorders.